2009
DOI: 10.1038/eye.2009.24
|View full text |Cite
|
Sign up to set email alerts
|

The application of stereotactic navigation surgery to orbital decompression for thyroid-associated orbitopathy

Abstract: Objectives To describe the application of stereotactic guidance, its preoperative workup, and limitations, if any, during orbital decompression surgery of the lateral orbital wall for thyroid-associated orbitopathy (TAO). Methods Case-controlled series of seven patients who underwent stereotactic-guided surgical navigation during external approach balanced orbital decompression with maximal debulking of the lateral wall. Results A progressive increase in debulking of the greater wing of sphenoid and exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 33 publications
(34 reference statements)
1
13
0
5
Order By: Relevance
“…This warranted the repositioning of the field generating magnet so that the computer system automatically could detect the instrument in use. Our conclusion was the same as Lee, Miller et al, who found that commonly encountered disadvantages of surgical navigation include learning curve, machine setup times, expense and equipment availability [6,7] .…”
Section: Discussionsupporting
confidence: 76%
“…This warranted the repositioning of the field generating magnet so that the computer system automatically could detect the instrument in use. Our conclusion was the same as Lee, Miller et al, who found that commonly encountered disadvantages of surgical navigation include learning curve, machine setup times, expense and equipment availability [6,7] .…”
Section: Discussionsupporting
confidence: 76%
“…Additional retroplacement of the globe can be achieved by combining the latter approach with intraorbital fat decompression 18. Stereotactic-guided navigation has been shown to be an asset in achieving safe and effective decompression of the deep lateral wall but is currently limited by its cost and availability 19 20…”
Section: Discussionmentioning
confidence: 99%
“…Whether stereotactic navigation in decompression surgery as described by Miller and Maloof [53] offers significant advantages remains to be proven. [22] the futility of attempting to remove masses of orbital fat has been proved ever since the account published by von Graefe in 1864.…”
Section: Isrn Ophthalmologymentioning
confidence: 99%